Ansiedade e consumo de substâncias psicoativas em adolescentes - Lopes, Andressa Pereira (2011)
The objectives of this study were: to relate psychoactive substance use and anxiety, to verify anxiety levels and the most consumed psychoactive substances, and to associate psychoactive substance use and anxiety among high school students from public and private schools in the city of Maceió. The students and institutions participating in the research were selected by non-probabilistic convenience sampling. It was a correlational design study. The sample consisted of 407 students, aged 14 to 18 years. The research was carried out in seven schools, four from the state public network and three from the private network. Participants answered a socio-demographic questionnaire; the Adolescent Anxiety Scale (EAA); and a questionnaire on psychoactive substance use. The relationship between psychoactive substance use and anxiety was analyzed by means of Fisher's chi-square and exact test. Alcohol was the most consumed licit substance by the students, while the solvent, the most consumed illicit substance by this group. Participants had a higher percentage at the moderate level: 28%. There was a statistically significant difference between psychoactive substance use and anxiety in adolescents. The lifetime use of solvents (p = 0.037) and energy sources (p = 0.023); use in the year of smoking (p = 0.043) and alcoholic beverages (p = 0.007); and frequent alcohol use (p <0.001) was related to moderate anxiety. There was a significant difference between psychoactive substance use and anxiety in school types: In the public school, there was a relationship between students who reported smoking in their lives and in the year, and between those who made use of solvents and energy drinks with severe anxiety (p = 0.022, p = 0.003, p = 0.010, p = 0 = 0.44, respectively); and among students who reported frequent consumption of alcohol with moderate anxiety (p = 0.007). In private school, there was a relationship between students consumed alcoholic beverages in the year with moderate anxiety (p = 0.011). The research verified the need to carry out drug prevention and health promotion projects that aim to increase reflection on lifestyle and anxiety. (AU)